The Impact of Teacher Talk Towards Students’ Language Attitude in Learning English Speaking Skill - Mangngemba, Sintike; Tandikombong, Matius; Panggua, Selvi (Pustaka Digital Indonesia, 2025)
This research is important due to the crucial role teacher talk plays in the process of learning English, particularly in developing students’ speaking skills. Students’ language attitudes towards speaking are strongly influenced by how teachers or lecturers communicate during the learning process. Therefore, understanding the impact of teacher talk on students’ language attitudes is urgent to ensure effective learning and improved outcomes. This study aims to investigate the effect of teacher talk on students’ language attitudes in learning English speaking skills. A quantitative method was employed, with convenience sampling used to collect data from 19 seventh-semester students in the English Education program who attended all speaking classes. Data were collected through questionnaires and analyzed using t-tests, Pearson product-moment correlation, coefficient of determination, and linear regression. The hypothesis testing showed a t-count value of 5.053, greater than the t-table value of 2.120, with a significance level of 0.000, below the 0.05 threshold. This means the Null Hypothesis (H0) is rejected, and the Alternative Hypothesis (Ha) is accepted, confirming a positive and significant impact of teacher talk on students’ language attitudes in learning speaking skills. The findings highlight teacher talk as an important factor in shaping language attitudes, suggesting lecturers need to design communication approaches effectively in English speaking classes to achieve better results.